MANIFEST CONFLICT BETWEEN ORGANIZERS AND PARTICIPANTS IN THE 2015-2016 REGIONAL HEAD ELECTION OF PEMATANGSIANTAR CITY - Lubis, Khairunnisah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2022)
The regional election directly has been done since june 2005. In addition, forthe first time also in the election disputes nomination a prolonged and lead to delayelection highest, namely to 11 months in pematangsiantar. Political conflicts theregional election describes two different purposes both in the committee andattendees. The political conflicts in the regional election that is characterized by thepresence of partiality the head elections the area of a city pematangsiantar to one ofthe pairs of candidates mayor and deputy mayor pematangsiantar 2015.Many thenegative effects of political conflict occurred in the town of pematangsiantar duringthe election process the head of the region especially in 2015 to 2016.This research uses the qualitative methodology to analyze the political conflictin Pematang Siantar City. This methodology aims to portray the real situation and findout the pattern of the conflict between the election committees and the candidatessince the election had been delayed for two times.This research concern of the pattern of the conflict of the mayoral election inPematang Siantar City from 2015 to 2016. The result finds out that the conflict wasclassified as the manifest and latent conflicts